2020
DOI: 10.1093/imrn/rnaa133
|View full text |Cite
|
Sign up to set email alerts
|

The Centre-Quotient Property and Weak Centrality forC*-Algebras

Abstract: We give a number of equivalent conditions (including weak centrality) for a general $C^*$-algebra to have the centre-quotient property. We show that every $C^*$-algebra $A$ has a largest weakly central ideal $J_{wc}(A)$. For an ideal $I$ of a unital $C^*$-algebra $A$, we find a necessary and sufficient condition for a central element of $A/I$ to lift to a central element of $A$. This leads to a characterisation of the set $V_A$ of elements of an arbitrary $C^*$-algebra $A$, which prevent $A$ from having the ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…By Remark 4.3 a state on is maximally mixed if and only if it is maximally mixed on . By [3, 3.10], the quotients of weakly central C-algebras are weakly central, so in particular is weakly central. In this way, we reduce the proof to the algebra (instead of ), which has strong radical .…”
Section: Maximally Mixed Statesmentioning
confidence: 99%
“…By Remark 4.3 a state on is maximally mixed if and only if it is maximally mixed on . By [3, 3.10], the quotients of weakly central C-algebras are weakly central, so in particular is weakly central. In this way, we reduce the proof to the algebra (instead of ), which has strong radical .…”
Section: Maximally Mixed Statesmentioning
confidence: 99%
“…By a well-known result of Vesterstrøm [24] a unital C * -algebra A is weakly central if and only if it satisfies the centre-quotient property (the CQ-property), that is for any closed two-sided ideal I of A, (Z(A) + I)/I = Z(A/I). Motivated by results in [9], where the setting is purely algebraic, the first two authors defined in [5] a local version of the CQ-property as follows. An element a ∈ A is called a CQ-element if for every closed two-sided ideal I of A, a + I ∈ Z(A/I) implies a ∈ Z(A) + I ([5, Definition 4.1]).…”
Section: Introductionmentioning
confidence: 99%
“…An element a ∈ A is called a CQ-element if for every closed two-sided ideal I of A, a + I ∈ Z(A/I) implies a ∈ Z(A) + I ([5, Definition 4.1]). In [5,Theorem 4.8], a description of the set CQ(A) of all CQ-elements of A was obtained in terms of those maximal ideals of A which witness the failure of the weak centrality of A. Further, it was shown that CQ(A) contains all commutators and products by quasinilpotent elements.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations